2018
DOI: 10.29252/shenakht.5.5.53
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of cognitive therapy based on mindfulness on positive affect, psychological flexibility and mind-awareness components of people With depression symptoms

Abstract: Introduction: Depression is recognized as one of the most common disabling and recurrent disorders with changes in emotional, cognitive, and neurobiological functions over a twoweekperiod. Aim: The purpose of this study was to determine the effectiveness of cognitive therapy based on mindfulness on positive affect, psychological flexibility and mind-awareness components of people with depression symptoms. Method: The research method was semi-experimental with control and experimental group as pre-test and post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The results indicated that mindfulness-based cognitive therapy significantly improves the quality of life and resilience in women with chronic pain, with an effect size of 0.75. These findings are consistent with the research prior (Day, 2014;Goudarzi, 2018;Kuyken, 2016;Malekpour Golsefidi, 2022;Nasrabadi, 2022;Zimmermann, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results indicated that mindfulness-based cognitive therapy significantly improves the quality of life and resilience in women with chronic pain, with an effect size of 0.75. These findings are consistent with the research prior (Day, 2014;Goudarzi, 2018;Kuyken, 2016;Malekpour Golsefidi, 2022;Nasrabadi, 2022;Zimmermann, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Mindfulness aims to teach control of attention, helping individuals to recognize minor mood changes and prevent the recurrence of their problems. Mindfulness therapy involves specific strategies to focus the attention process, which in turn helps prevent negative moods, negative thoughts, tendencies towards anxious responses, and fosters the development of new perspectives and the formation of pleasant thoughts and emotions (Goudarzi, 2018). Mindfulness training, through breathing and using body parts, awareness of events, and body awareness, voice breathing, and thoughts and acceptance of thoughts, leads to a change in the emotional and emotional meanings of the individual, making them realize that their thoughts, rather than being a reflection of reality, are incorrect thoughts that lead to anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conscious awareness creates lasting effects on couples to solve problems with respect, intimacy, and empathy. Finally, it can be said that people, as a result of cognitive-mindedness treatment, accept experiences as separate elements from themselves and as a transient state and as a subject for change, and so instead of exploring the subject or cognitively or behaviorally avoiding the experience, which will both be painful, they accept and eventually internalize these experiences, like other experiences that are neutral or not emotionally charged [26,27]. as a defense, it can be explained.…”
Section: Discussionmentioning
confidence: 99%